Evaluation of the BEAT Meth Intervention for Emergency Department Patients with Methamphetamine Psychosis. Issue 1 (8th January 2023) - Simpson, Scott A.; Wolf, Chelsea; Loh, Ryan M.; Camfield, Katherine; Rylander, Melanie
Abstract : Objectives: Methamphetamine is the second leading cause of overdose death in America and a leading cause of emergency department (ED) visits. Methamphetamine-induced psychosis is a dangerous and difficult-to-treat consequence of methamphetamine use. We describe the pilot implementation and outcomes of a multimodal treatment intervention for ED patients with methamphetamine psychosis, Beginning Early and Assertive Treatment for Methamphetamine Psychosis (BEAT Meth). Methods: BEAT Meth was implemented in an urban safety net health system. The protocol includes early identification and treatment of methamphetamine psychosis, a protocolized hospitalization, and support for transitioning patients to specialty addiction treatment. Patients receiving BEAT Meth were compared with ED patients with methamphetamine psychosis who were discharged. Implementation fidelity was measured to assess feasibility. Results: BEAT Meth patients were nearly 3 times more likely to attend an outpatient specialty addiction appointment in the 30 days after discharge than comparison patients (32% vs 11%, P < 0.01). Subsequent ED utilization was common among all patients, and there was no significant difference in 30-day ED return rates between BEAT Meth and comparison patients (28% vs 37%, P = 0.10). Exploratory analyses suggested that increased attendance at outpatient treatment reduced ED utilization. Conclusions: BEAT Meth is an intervention framework to support identification, management, and treatment engagement of ED patients with methamphetamine psychosis. Treatment strategies like BEAT Meth are necessary to manage the unique challenges of methamphetamine addiction. These findings will guide clinical care, program development, and research.